2018
DOI: 10.3329/jbcbm.v4i2.39850
|View full text |Cite
|
Sign up to set email alerts
|

Influence of organic manures on the growth of diabetes preventive medicinal plant Gynura, Gynura procumbens

Abstract: A pot experiment was carried out to evaluate the effects of various organic manures on the growth performance and biomass production of Gynura procumbens in the net house of the Department of Soil, Water and Environment, University of Dhaka. Seven types of manures, viz. ACI, BGF-1, Mazim, Vermicompost, Sufola, GTS and Poultry litter composts were used separately at the rate of 15 ton/ha. Highest height (78cm) in poultry litter compost, leaf number (208.33 no./plant) in sufola manure, leaf area (53.64 cm 2 /pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Brady and Weil (2002) concluded that the organic manures contain a passive fraction of 60 to 90 per cent which is very slowly available to plants. Akon et al (2018) found that height, leaf area, and fresh and dry weights of leaf of Gynura procumbens varied significantly (p ≤ 0.5) under seven types of manures including vermicompost. Protein content in leaf is presented in Table 2 where maximum and minimum amount of protein was achieved in VC 15 P 10 K 20 and control treatment (VC 0 P 0 K 0 ), respectively.…”
Section: Resultsmentioning
confidence: 94%
“…Brady and Weil (2002) concluded that the organic manures contain a passive fraction of 60 to 90 per cent which is very slowly available to plants. Akon et al (2018) found that height, leaf area, and fresh and dry weights of leaf of Gynura procumbens varied significantly (p ≤ 0.5) under seven types of manures including vermicompost. Protein content in leaf is presented in Table 2 where maximum and minimum amount of protein was achieved in VC 15 P 10 K 20 and control treatment (VC 0 P 0 K 0 ), respectively.…”
Section: Resultsmentioning
confidence: 94%
“…Brady and Weil (27) concluded that the organic manures contain a passive fraction of 60 to 90 per cent which is very slowly available to plants. Akon et al (28) observed that height, leaf area, and fresh and dry weights of leaf of Gynura procunbens varied significantly (p < 0.05) under seven types of manures. Magomya et al (23) collected ten different plant samples from wild and farmland of Nizeria viz.…”
Section: Protein Content In Leafmentioning
confidence: 99%
“…In fact, the results of some of the organic manures were relatively lower than those of the control. This could be attributed to failure to maintain a standard fertilizer grade by some organic fertilizer manufacturers in Bangladesh as pointed out by Akon et al (2018), leading to uniform availability of nutrients not being assured. Besides, there are factors in the environment, such as microbes, temperature and light intensity, which also influence the growth of the plants (Akon et al 2018).…”
Section: Nutrient Uptakementioning
confidence: 99%
“…This could be attributed to failure to maintain a standard fertilizer grade by some organic fertilizer manufacturers in Bangladesh as pointed out by Akon et al (2018), leading to uniform availability of nutrients not being assured. Besides, there are factors in the environment, such as microbes, temperature and light intensity, which also influence the growth of the plants (Akon et al 2018). Nonetheless, if the organic manure companies are to be compared, Kazi treated plants showed poor growth performance, which has been supported by low nutrient accumulation (3.96 mg plant -1 ) in their leaves, despite the fertilizer having relatively higher contents of N, P, K, S and Fe among other fertilizer companies.…”
Section: Nutrient Uptakementioning
confidence: 99%